Comparison of Functional Outcome of closed Retrograde Nailing and Mippo (Minimally Invasive Percutaneous Plate Osteshnthesis) Distal Femoral Locking Plate Fixation for Distal Femoral Fractures - Muhammad Imran Haider, Kashif Siddiq, Ahmad Jamal, Muhamad Adeel Razzaque, Adnan Nazir, Muhammad Imran Anjum, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of our study is to compare the safety and efficacy of MIPPO distal femoral locking plate versus retrograde nailing in distal locking plate fixation among patients suffering from distal femoral fractures. Study Design: Quasi Experimental study Place and Duration: Nishtar Hospital Multan. August 2021-May 2022 Methods: There were 112 patients of both genders with ages 15-48 years had distal femoral fractures and underwent for surgery were included in this study. After obtaining informed written consent, demographically detailed of enrolled cases were recorded. Causes of distal femoral fractures were assessed. Patients were equally categorized in two group. 56 patients in group O received MIPPO DFLP and in group P 56 cases received retrograde nailing. All patients were radiographed and categorized according on the criteria established by the AO/OTA categorization system.[13] Outcomes among both groups were assessed and compared in terms surgery duration, efficacy and complications. HSS score was used to describe effectiveness of both groups. SPSS 24.0 was used to analyze all data. Results: We found that males were higher in numbers 80 (71.4%) than females (32 (28.6%). Mean age of the included patients were 29.5±9.81 years and had mean BMI 24.8±11.44 kg/m2. Most common cause of fracture was road traffic accident (RTA) in 51 (45.5%) cases, followed by falling in 35 (31.3%) cases, sports in 17 (15.2%) cases and violence in 9 (8.04%). Most common affected side was right. As per AO classification, numbers were higher in Type 43A1 classification found in 65 (58.04%) cases. Mean union time in group O was lower 2.5±4.87 months as compared to group P 3.9±6.54 significantly with p value <0.005. We found significantly higher number of excellent results in MIPPO DFLP group found in 29 (51.8%) cases as compared to retrograde nailing group in 14 (25%) cases with p value <0.003. Complications (delayed union, non-union, deformity, bone stiffness) were found higher in group P. Conclusion: We concluded in this study that use of MIPPO DFLP for the treatment of distal third femoral shaft fractures is highly effective and useful as compared to retrograde nailing with p value <0.04 in terms of less unions time, higher excellent results and lower number of complications. Keywords: Retrograde Nailing, Distal Femoral Fractures, MIPPO DFLP, Efficacy, Complications